Response of Fertility Levels and Seeding Rates on Production Potential and Moisture use Efficiency of Linseed under Foot Hill Condition of Nagaland - Kumar, Rakesh; Deka, Bidyut C. (Indian Journal of Hill Farming, 2016)
Field experiments as carried out during the rabi season of 2010-11 and 2011-12 at Agricultural Research Farm of ICAR RC for NEH Region, Jharnapani to study the effect of fertility levels and seeding rates on productivity, profitability and moisture use efficiency of linseed under the rainfed condition of Nagaland. The yield and economics of linseed crop were significantly increased up to the application of 80-60-60-40 kg NPKS ha-1 but it was statistically at par with 60-45-45-30 kg NPKS ha-1. Highest moisture depletion, consumptive use, moisture efficiency, total and effective rainfall use efficiency was recorded under the application of 80-60-60-40 kg NPKS ha-1. Similarly, the maximum seed yield, economics, moisture use efficiency was also obtained with the plant density of 35 kg seed rate ha-1.